2005
DOI: 10.1177/003693300505000304
|View full text |Cite
|
Sign up to set email alerts
|

Admission Proforma Significantly Improves the Medical Record

Abstract: The authors worked in a busy regional fracture unit, where it was noted that important data was being omitted from medical notes. In an attempt to improve on this, an admission proforma was formulated. This was designed to be easily and quickly completed. Notes were audited on two separate weeks, the first before, and the second after introduction of the proforma. The overall results demonstrate statistically significant improvements in documentation with a proforma, and concur with the limited previous litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 2 publications
3
6
0
Order By: Relevance
“…We also assessed whether the implementation of a proforma makes it easier for healthcare professional to take coherent notes. This study illustrates that a surgical clerking proforma improves the quality of patient documentation, which is consistent with previous studies [2], [7], [8], [9].…”
Section: Discussionsupporting
confidence: 92%
“…We also assessed whether the implementation of a proforma makes it easier for healthcare professional to take coherent notes. This study illustrates that a surgical clerking proforma improves the quality of patient documentation, which is consistent with previous studies [2], [7], [8], [9].…”
Section: Discussionsupporting
confidence: 92%
“…While no study, to our knowledge, has previously looked at the use of customised diagrams, this result is consistent with previous findings, which have shown that the use of preprinted proformas improves the quality of documentation during admission 3 4. There is also evidence that structured documentation improves legibility and thus enhances the interpretation of clinical records 5 6.…”
Section: Discussionsupporting
confidence: 90%
“…Contributing factors include limited time available for clerking new patients, and numerous demands placed on junior doctors responsible for ensuring that wards run smoothly. [12] One way to address these issues is to produce standardised preprinted medical admission sheets for junior doctors to use as prompting tools. Many studies have provided Table 2 evidence that preprinted pro formas for patient admission are effective in overcoming problems with incomplete medical records.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have provided Table 2 evidence that preprinted pro formas for patient admission are effective in overcoming problems with incomplete medical records. Not only do these forms increase data capture, [12][13][14] but they also make the process of gathering clinical information at the point of admission more efficient and less time-consuming. These findings have been replicated in hospitals across the world, including in Africa.…”
Section: Discussionmentioning
confidence: 99%